AN OPTIMIZED KINETIC SPECTROPHOTOMETRIC METHOD FOR THE RAPID AND ACCURATE DETERMINATION OF CEFOPERAZONE IN URINE AND TAP WATER SAMPLES - SOTO, CESAR; Saavedra, Renato; Contreras, David; Oyarzún, Diego; Poza, Cristián (Journal of the Chilean Chemical Society, 2025)
This study presents a new approach for quantifying the antibiotic cefoperazone (CPZ) in spiked urine and tap water samples using an indirect kinetic spectrophotometry method. The method involves the oxidation of CPZ by permanganate (MnO4-) in an alkaline media. The progress of the reaction is monitored by tracking the increase in manganate (MnO42- ) at 610 nm. The optimization of chemical-dependent variables was achieved through the utilization of multivariate statistical methods. The optimized values were 5 minutes of reaction time, KMnO4 of 1.11 · 10 -3 mol L−1, and NaOH of 0.27 mol L−1. Under these conditions, calibration curves were constructed. The detection limits obtained in urine and tap water spiked samples were 3.75 · 10−7 mol L−1 and 3.74 · 10−7 mol L−1, respectively. The results showed that intraday and interday recoveries ranged from 98.25 to 102.7%, indicating acceptable differences between observed and expected values according to the confidence percentage established as a criterion of acceptability; thus, demonstrating repeatability in results as well as satisfactory accuracy for this kinetic analytical method.